Measuring Infant and Young Child Complementary Feeding Practices: Indicators, Current Practice and Research Gaps - Ruel, Marie T. (2016)
In this presentation, Dr. Marie Ruel, Director of the Poverty, Health, and Nutrition Divisions of the International Food Policy Research Institute (IFPRI) tackles the important issue of how to measure infant and young child feeding practices, as they relate to child nutrition. She explains indicators, current practices, and research gaps. Dr. Ruel also serves as leader of the research flagship on integrated nutrition programs and policies for the CGIAR Research Program on Agriculture for Nutrition and Health (A4NH), led by IFPRI. This presentation was delivered at the 87th Nestle Nutrition Institute Workshop in Singapore May 8-11, 2016. For more information on child nutrition research, please visit ifpri.org or a4nh.cgiar.org.